Geographical analysis of the problems facing the development of ecotourism in Choman district - Ahmed, Asst.L.Ahmed Saeed; Mohammed, Asst.L.Mustafa Yousef; Qadir, Asst.L.Didar Hamad; Ahmad, Sangar Mahmoud (Sulaimani Journal for Humanities, 2025)
Choman district possesses abundant natural features that make it highly suitable for the development of eco-tourism. However, despite these favorable characteristics, several challenges hinder the growth of this vital sector. Therefore, this study focuses on a geographical analysis of the problems facing the development of eco-tourism in Choman district, with specific attention to the areas of Przhe, Bekodian Lake, and Kanya Rash. The main objective of the study is to identify the obstacles to eco-tourism development and to shed light on the future potential of eco-tourism in the region. The research employs both descriptive and analytical methods, supported by fieldwork, including site visits and the distribution of survey forms. Finally, the research concluded that the primary obstacle to the development of eco-tourism in the study area lies in the weakness of the economic infrastructure in general, and the inadequacy of road networks in particular.
Keywords: Tourism; Ecotourism; Choman District; Development; Tourism Development